Relative supersaturation values distinguish between feline urinary and non-urinary foods and align with expected urine analytes contributions to uroliths - Morris, Elizabeth M.; McGrath, Allison P.; Brejda, John; Jewell, Dennis E. (Frontiers in Veterinary Science, 2023)
Introduction: Uroliths are concretions formed in the urinary tract. These can be problematic in humans and companion animals such as cats. Magnesium ammonium phosphate (struvite) and calcium oxalate (CaOx) are the most common forms of uroliths. The relative supersaturation (RSS) is a relative risk index of crystal formation. Here, an updated program for calculating RSS, EQUIL-HL21, was used to detect differences in RSS values when cats were fed foods formulated for urinary and non-urinary conditions. In addition, the contributions of urinary analytes to RSS values were examined via regression analyses. Methods: Historical data from feeding trials including foods indicated for use in urinary or non-urinary conditions were analyzed for nutrient composition and urinary parameters. RSS was calculated by EQUIL-HL21. The relationship between RSS values calculated by EQUIL-HL21 and urinary analytes was examined by regression models, which were selected by R2 and stepwise methods. Results: Cats that consumed urinary foods had significantly greater levels of urinary sodium and chloride compared with those that consumed non-urinary foods, consistent with the greater amounts of sodium and chloride in the urinary foods. Those that consumed non-urinary foods had higher urine pH, ammonium, potassium, phosphorus, magnesium, oxalate, citrate, and sulfate. Struvite RSS value and number of urinary crystals were significantly lower in cats fed the urinary foods. Mean CaOx RSS values were similar in both foods, though the number of CaOx crystals were significantly higher in cats that consumed non-urinary foods. A model predicting the natural log of struvite RSS values indicated that these values would increase with increasing urine pH, ammonium, chloride, calcium, phosphorus, and magnesium, and would decrease with increasing urine citrate and sulfate. CaOx RSS was predicted to increase as urinary chloride, calcium, and oxalates increased, and would decrease as urine pH, sodium, phosphorus, citrate, and sulfate increased. Discussion: These analyses demonstrate that the EQUIL-HL21 program can accurately detect expected differences between foods formulated for urinary and non-urinary indications. Regression models showed the eight urinary analytes that respectively contribute to the predicted RSS values for struvite and CaOx.